The Relationship Between Economic Indicators and Suicide Rate in Turkey: An Econometric Analysis - Ümit Çıraklı (Association of Nurse Managers, 2020)
INTRODUCTION: The aim of this study is to reveal the relationship between national economic indicators and suicide rate and, whether the changes in macroeconomic factors affect suicide rate in Turkey. METHODS: In this context, real GDP, unemployment, inflation and crude suicide rate between 1974 and 2015 were examined using the ARDL (Autoregressive Distributed Lag) bounds testing approach. RESULTS: It was found that inflation and unemployment did not have a statistically significant effect on crude suicide rate (p> 0.05). There was a statistically significant (p=0.000) and direct relationship (0.453) between real GDP and crude suicide rate in the long term. In terms of the effects of economic crises on the crude suicide rate, it was found that only the 1994 and 2001 economic crises had a significant negative impact on the suicide rate (p> 0.05). DISCUSSION AND CONCLUSION: As a result of the study, it is concluded that economic growth in terms of real GDP has an adverse effect on mental health. Also it is conluded that economic crises have mostly negative effects on crude suicide rates in terms of mental health.